An Analysis Students’ Perception Of Watching English Videos In Speaking Skills At Eleventh Grade Of Sma Budisatrya Medan In Academic Year 2021-2022 - Nia Safira Hardi, M. Khalid (Ability: Journal of Education and Social Analysis, 2023)
There are still many students who do not have adequate speaking skills so they need the right techniques or learning methods that can help improve their speaking skills. One way that is not boring is to watch English videos as a tool to understand the content of the story and learn the language used in the story. The purpose of this study was to determine students' perceptions of English videos in speaking skills. Qualitative methods are used in this study. The subjects of this study were 10 students from class XI IPA 1. The data collection technique used interviews where students were interviewed after finishing speaking class. Perception is the process of receiving stimuli (objects, qualities, relationships between symptoms, and events) until the stimulus is realized and understood. Because perception is not just sensing, there are writers who state perception as the interpretation of experience. Students' perceptions of watching English videos are very interested because they are easy to understand through videos, there are movements, subtitles and how to pronounce them so that students can better understand the contents of the video. In addition, watching English videos can improve students' speaking skills such as adding new vocabulary in everyday life, adding new insights and increasing speaking skills. Then all the data shows that students often watch English videos given by the teacher in the classroom as learning media. So, this research is in accordance with students' perceptions of watching English videos in speaking skills.